Tendências de extremos climáticos e suas relações com a temperatura dos oceanos tropicais na região Centro-Oeste do Brasil - Santos, Luiz Octávio Fabricio dos (2021)
Climatic extremes have been a subject of great importance in the context of climate change, as their understanding provides information for the management of events that can lead to natural disasters and socioeconomic imbalances. The objective of this study was to characterize the trend of extreme climatic events of air temperature and precipitation in the Midwest region of Brazil, as well as to analyze their relationship with sea surface temperature anomalies in the Pacific and Atlantic oceans. Precipitation and air temperature data were collected from 24 conventional meteorological stations from 1979 to 2019. Moreover, data on sea surface temperature anomalies were used in Niño 1 + 2, Niño 3, Niño 3.4, Niño 4, North and South Atlantic areas in the period from 1979 to 2019. The monotonic tendencies of extreme climatic indices were calculated using the Mann-Kendall test. The independence of the data series was verified using the Autocorrelation function. Pearson's correlation method was used to assess the degree of relationship between the extreme climatic indexes of air temperature and precipitation with the annual anomalies of sea surface temperature. There was a positive trend in air temperature during hot days and nights, while on cold days and nights this trend was negative. Maximum and minimum temperatures have increased in much of the Midwest region. In addition, the maximum temperature is increasing with greater magnitude than the minimum temperature. On the other hand, the extreme climatic indexes of precipitation did not present a well-defined pattern, however, the events with strong precipitation presented tendencies of increase. It is noteworthy that the simple index of daily precipitation showed the greatest tendency to increase, which indicates that the average intensity of precipitation intensified during the analyzed period. The anomalies of sea surface temperature in the Equatorial and Atlantic Pacific Ocean showed statistically significant correlations with extreme climatic indices, indicating that the variability of sea surface temperature influences the behavior of air temperature and precipitation over the Midwest of Brazil. Therefore, trends in climatic events were observed for air temperature and precipitation for the Midwest region of Brazil, which were significantly correlated with surface temperature anomalies in the Pacific and Atlantic oceans.